Are immigrants particularly entrepreneurial? Policy lessons from a selective immigration system - David A. Green; Huju Liu; Yuri Ostrovsky; Garnett Picot (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
Firm ownership is a defining feature of immigrant adaptation with 41% of immigrants owning a firm at some point in their first 10 years after arrival. We use rich Canadian administrative data linking immigrant arrival records with individual and firm tax data to examine the process by which immigrants enter firm ownership. We find that higher immigrant firm ownership rates are almost entirely associated with nonincorporated firm ownership, which looks like a state of last resort. Human capital plays no role in the opening of preferable incorporated firms. On balance, immigrants are not more entrepreneurial in terms of opening incorporated firms with employees and standard policy levers appear to have limited effect on this.
Keywords: 330